The Development Model of Woman Empowerment in Order to Increase Family’s Food Tenacity - Eny Yuniriyanti; Ririn Sudarwati (Jurnal Ekonomi dan Studi Pembangunan, 2017)
This research is conducted with the intention to find the design of women empowerment role model in the attempt of increasing family food security. This finding will be utilized as the basic development plan which related to the efforts of achieving the family food security on the basis of local wisdom. By applying the questionnaire survey method, questionnaire will be analyzed by the descriptive analysis, correlation analysis, and crosstab analysis. The result of research shows that the attempt of family food security in the highest priority is to divert or to switch the staple food from rice to the other type of cheaper staple food (for instance corn). This a very common condition as the most easily found and bought staple food, to substitute rice, is corn. Meanwhile the most consumed side dishes in our society are the soybean cake (tempe) and tofu (tahu), while chicken and other meats are the less consumable side dishes in our society. For vegetable, Spinach is the most consumed vegetable as this species is easy to be planted around the house/yard. Based on the pre-set criteria, the condition of family food security in the research locations are 16% in secured level and the rest, 84%, is in insecured level.Keywords: Dasa Wisma PKK, The Family Food Security, local wisdom.JEL Classification: O12, P46